AI in academic writing: Assessing current usage and future implications - Rabbianty, Eva Nikmatul; Azizah, Siti; Virdyna, Nina Khayatul (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2023)
Artificial intelligence (AI) integration in academic writing has gained significant attention due to its potential impact on authorship, the natural character of academic works, and ethical considerations. This Study aims to assess the faculty members' perceptions on their current usage of AI in academic writing and explore its future implications. The research involved an online survey administered to 68 faculty members responding to closed and open-ended questions. The study revealed faculty members' perceptions of AI integration in academic writing and its implications for authorship and the authenticity of academic work. Findings reveal widespread adoption of AI tools among faculty members, offering efficiency, productivity, and accuracy benefits in areas like grammar checks, reference management, writing assistance, and plagiarism detection. However, concerns arise over authorship preservation and maintaining academic work's unique character, emphasizing the need for clear guidelines. Ethical considerations and best practices are also highlighted to use AI while safeguarding academic integrity effectively. These insights extend to educators, policy makers, and researchers, offering a comprehensive view of AI's current role in academic writing and guiding ethical discussions and best practices. Ultimately, this research enhances teaching and learning practices in Indonesian higher education institutions through responsible AI integration.